EFFECT OF SGLT2 INHIBITOR DAPAGLIFLOZIN ON SODIUM, POTASSIUM AND CREATININE LEVELS IN PATIENTS WITH ACUTE HEART FAILURE - Fatima Gilani, Fauzia; Shabana Ali,; Mudassar Noor,; Kulsoom Farhat,; Muhammad Bilal Siddique,; Maryam Fatima, (Journal of Ayub Medical College Abbottabad, 2024)
Background: Sodium-glucose co-transporter 2 inhibitors (SGLT2i) is a new class of medication for the treatment of type 2 diabetes mellitus. Additionally, they have been found to have beneficial effects on heart failure outcomes, convincingly reducing the morbidity and mortality in heart failure. Although the medical data indicates SGLT2i to be safe and cardio-protective, very little attention has been given to the impact of these agents on electrolyte balance particularly in acute heart failure (AHF). We aimed to evaluate the effect of SGLT2i, and dapagliflozin on serum sodium, potassium and creatinine in AHF. Methods: Overall, 160 adult patients of either gender, admitted with AHF were selected for the study. Selected individuals were randomly assigned to receive dapagliflozin 10 mg orally added to standard medical treatment (n=80) or were in reception of standard medical therapy only (n=80). Serum electrolytes and serum creatinine were collected on admission and day 7 or on discharge whichever happened earlier. Results: The mean level of serum electrolytes displayed insignificant differences among both groups on admission. The mean level of serum potassium was higher in the dapagliflozin group compared with the control group (p<0.001) on day 7/discharge. Mean serum sodium level was comparable and showed significant differences between the two groups following treatment (p-value=0.021). Significant higher levels of serum creatinine were observed following treatment in both groups. However, on intergroup comparison, they were statistically insignificant. Conclusion: Dapagliflozin is an effective treatment of heart failure and is not associated with deterioration of serum electrolyte levels and renal functioning when used as add-on therapy in AHF.